Long‐term Follow‐up Helicobacter Pylori Reinfection Rate and Its Associated Factors in Korea. Issue 2 (8th October 2012) - Kim, Min Soo; Kim, Nayoung; Kim, Sung Eun; Jo, Hyun Jin; Shin, Cheol Min; Lee, Sang Hyub; Park, Young Soo; Hwang, Jin‐Hyeok; Kim, Jin‐Wook; Jeong, Sook‐Hyang; Lee, Dong Ho; Kim, Jung Mogg; et al.
Abstract Background The reinfection rate of Helicobacter pylori has been reported to be low in developed countries but high in developing countries. The aim of this study is to evaluate the long‐term reinfection rate of H. pylori and to investigate its associated risk factors in South Korea. Methods During 2003–2010, H. pylori‐positive 970 patients received standard proton pump inhibitor (PPI)‐based triple eradication therapy, and follow‐up H. pylori tests were performed with 13C urea breath test or invasive tests (Giemsa histology, CLO test, and culture) 4 weeks after completion of treatment. A total of 331 patients who were maintained an H. pylori‐eradicated state at 1 year after eradication were divided into two groups according to reinfection. For the evaluation of risk factors of reinfection, gender, age, smoking, alcohol, income, education, gastrointestinal symptoms, clinical diagnosis, histologic atrophic gastritis or intestinal metaplasia, and clarithromycin resistance were analyzed. Results The follow‐up period was 18–95 months (mean: 37.1 months), and H. pylori reappeared in 36 of 331 patients (10.9%), resulting in the annual reinfection rate of 3.51% per year. Multivariate analysis showed that male gender (HR 2.28; 95% CI, 1.05–5.00, p = .037) and low monthly family income (≤5000$ vs >5000$) (HR 3.54; 95% CI, 1.08–11.67, p = .038) were associated with H. pylori reinfection. Conclusion This long‐term reinfection rate of H. pylori stayed rather low (3.51% per year), and male and low income determined the reinfection, factors already known to be important for H. pylori infection.